Rutin Inhibits Streptococcus suis Biofilm Formation by Affecting CPS Biosynthesis - Wang, Shuai; Wang, Chang; Gao, Lingfei; Cai, Hua; Zhou, Yonghui; Yang, Yanbei; Xu, Changgeng; Ding, Wenya; Chen, Jianqing; Muhammad, Ishfaq; Chen, Xueying; He, Xinmiao; et al. (Frontiers in Pharmacology, 2017)
Streptococcus suis (S. suis) is an important zoonotic pathogen that causes severe diseases in humans and pigs. Microbial biofilms are communities of surface-adhered cells enclosed in a matrix of extracellular polymeric substances. Treatments with antibiotics or biocides are often ineffective in eradicating biofilms. Promising alternatives to conventional agents are biofilm-inhibiting compounds regulating biofilm development without impairing growth. Here, we screened a S. suis biofilm inhibitor, rutin, derived from Syringa. Rutin, a kind of flavonoids, shows efficient biofilm inhibition of S. suis without impairing its growth. Capsular polysaccharides（CPS） are reported to be involved in the bacterial adherence to influence bacterial biofilm formation. We investigated the effect of rutin on S. suis CPS content and structure. The results showed that rutin was beneficial to improve the CPS content of S. suis without changing its structure. We further provided evidence that rutin specifically affected S. suis biofilm susceptibility by affecting cps biosynthesis in vitro. The study explores the antibiofilm potential of rutin against S. suis which can be used as an adhesion inhibitor for the prevention of S. suis biofilm-related infections. The ability of rutin to inhibit S. suis biofilm formation and its molecular mechanism opens new possibilities for pharmacological and industrial applications.